Interval to closure of ‘temporary' stomas in the Groote Schuur hospital trauma centre - Abshina, Fathi (Division of General Surgery, 2024)
BACKGROUND: A significant percentage of temporary stomas placed for trauma reasons are never reversed, leading to a significant effect on quality of life, a profound impact on physical and psychological well-being, and additional strain on the healthcare budget (1). This study aimed to evaluate the interval between temporary stoma creation and closure in trauma patients at Groote Schuur Hospital (GSH) trauma centre using secondary measures such as: • Interval to loopogram (an X-ray examination in which contrast (X-ray dye) is introduced into the stoma to visualize the bowel part that extends to the stoma) • Identifying reasons for the delay in closure. • Evaluating complications after stoma creation or closure. METHODOLOGY: The study design comprised a retrospective descriptive cohort study conducted over 11 years from 2010 to 2020 at the GSH trauma center, in the Western Cape, South Africa. The files of all patients over the age of 13 years with a temporary stoma as a result of trauma were reviewed. RESULTS: The study included 199 patients. The majority were males [N=182 (91%)], with a mean age of 30 years (range from 18 to 61) The most common type of stoma created was a loop stoma [N=139 (70%)]. The overall stoma closure rate was 66% (N=132) and the mean duration from stoma creation to closure was approximately 66 weeks (range 304.7 weeks with min 5 weeks to max 310 weeks,mode 29,4 weeks,median 55.1 weeks). About 47% of patients experienced no delay (reversed on appointment dates), while 53% were delayed due to various reasons. Among the 73 patients who participated in the telephonic survey, 77.46% reported stoma reversal. Most patients (81.16%) were aware that their stoma needed to be reversed, and 73.91% attended their follow-up appointment. Furthermore, 41.43% experienced complications secondary to their stoma. The majority of the 73 patients who responded to the survey, knew how to manage their stomas. The survey was mainly conducted as part of a study to determine the reasons behind the delay of closure as certain information was missing from patient's files. CONCLUSION: These findings highlight the importance of increasing efforts to eliminate stoma reversal delays, as well as improving patient follow-up and stoma care education.